Characteristics of ocular findings of patients with coronavirus disease 2019 in China - Shudan Wang; Jiaoyang Feng; Rui Zhu; Xin Jin; Yiheng Ding; Di Jin; Yu Guo; Hong Zhang (Frontiers in Medicine)
PurposeThis study aimed to report the ocular manifestations in individuals with coronavirus disease 2019 (COVID-19) and investigate any correlation between the occurrence of ocular symptoms and systemic symptoms.MethodsA retrospective electronic survey was conducted among the general public in northern China from December 2022 through February 2023. Inclusion criteria for COVID-19 was confirmed testing positive via a polymerase chain reaction (PCR) test or testing positive for COVID-19 via an antigen kit. The anonymous survey collected information on demographics, systemic COVID-19 symptoms, ocular diagnosis and symptoms, comorbidities and disease history.ResultsA total of 2,405 survey responses were collected and the final analysis included individuals in the 335 COVID-19 positive group and 434 individuals in the COVID-19 negative group. Among COVID-19 positive patients 66.3% (n = 222) reported experiencing ocular symptoms. Dryness (n = 106, 31.6%), blurred vision (n = 81, 24.2%), eye pain (n = 72, 21.5%), and itching (n = 71, 21.2%) were the main features. COVID-19 was found to be associated with a higher prevalence of conjunctivitis, iritis, uveitis, retinal vein occlusion and optic neuritis. The majority of individuals (51.0%) developed eye symptoms after the onset of COVID-19 systemic symptoms. There was no significant association between the severity of systemic symptoms and ocular symptoms.ConclusionIndividuals with COVID-19 were significantly more likely to experience ocular symptoms. COVID-19 was found to be associated with a higher prevalence of retinal diseases. The majority of individuals developed ocular symptoms right after the onset of systemic symptoms.